2020
DOI: 10.3390/met10040546
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Tool Offset on the Microstructure and Properties of AA6061/AZ31B Friction Stir Welding Joints

Abstract: Friction stir welding was carried out on AA6061/AZ31B alloy, and the influence of tool offset on microstructures and mechanical properties of the joints was studied. The results showed that preferred properties were obtained when Mg was placed in the Advancing Side (AS) and offset was positioned into Mg. The distribution of Al3Mg2 and Al12Mg17 intermetallic compounds (IMCs) could be improved with offset in a certain range. The tensile strength of the joints was elevated with the increase of the offset due to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 20 publications
2
4
0
Order By: Relevance
“…Sameer et al [14] studied the influence of the advancing side (AS) material on the distribution of the IMCs, and the results indicated that the IMCs layer was thinner when magnesium alloy was placed in the AS. Similar observations were obtained by Liu et al [15]. In the FSW process of dissimilar alloys, the full mixing of materials is accelerated by placing the matrix with poor plastic and ductility in the AS.…”
Section: Introductionsupporting
confidence: 87%
See 1 more Smart Citation
“…Sameer et al [14] studied the influence of the advancing side (AS) material on the distribution of the IMCs, and the results indicated that the IMCs layer was thinner when magnesium alloy was placed in the AS. Similar observations were obtained by Liu et al [15]. In the FSW process of dissimilar alloys, the full mixing of materials is accelerated by placing the matrix with poor plastic and ductility in the AS.…”
Section: Introductionsupporting
confidence: 87%
“…Similar observations were obtained by Liu et al. [15]. In the FSW process of dissimilar alloys, the full mixing of materials is accelerated by placing the matrix with poor plastic and ductility in the AS.…”
Section: Introductionsupporting
confidence: 86%
“…In dissimilar Al-Mg alloys welding process, the hardness was 86 Hv for Mg alloy set near the leading edge and 89 Hv for Mg alloy set on the trailing edge, this small modification on hardness value was due to material flow and IMC stream of Al and Mg [20]. The internal heat was reduced when increasing the tool offset to the Mg plate and the morphology of IMCs was distributed more homogeneous and the hardness value was declined [18]. The strong ultrasonic vibration can break the IMCs into fragments and enhance the finer grain size compared to conventional FSW and the mean hardness value of NZ was significantly increased [19].…”
Section: Analysis Of Microhardnessmentioning
confidence: 97%
“…The FSW process establishes different joining mechanisms in different joining configurations. In the overlap configuration, for example, the mechanical interlock plays the most important role in joining [10], although it has been reported that a metallurgical bond prevails when the FSW tool does not touch the lower layer [11]. The T configuration has recently attracted a lot of attention due to its greater potential for structural applications [12].…”
Section: Introductionmentioning
confidence: 99%